Development and performance evaluation of garlic (Allium sativum) stalk cutter-cum-grader - SINGH, CHARAN; SINGH, VIJAY KUMAR; KUMAR, RAVI; NEHA,; GARG, MUKESH KUMAR; KUMAR, VIKASH; JOSHI, NIRAV UMESHBHAI; POPALIYA, CHANDANI (The Indian Journal of Agricultural Sciences, 2022)
The manual stalk cutting and grading of garlic (Allium sativum L.) is inconsistent, inefficient and demands skilled labour. A garlic stalk cutter-cum-grader was developed at the Department of Processing and Food Engineering, CCS Haryana Agricultural University, Hisar, Haryana during 2018–19, along with performance evaluation and optimization of working parameters using response surface methodology. The machine comprises of four major units, viz. cutting unit, grading unit, reciprocating assembly and a transmission system. The performance evaluation indicated that there was a significant effect of feed (2, 3, 4, 5 and 6 stalks) and moisture content (14, 21, 28, 35 and 42 (±1% in all levels, wet bulb) of the stalk on the performance parameters. The capacity of the machine increased with moisture content and feed rate. The grading efficiency first increased and then decreased with moisture content, whereas it decreased with an increase in feed rate. The bulb damage increased with a decrease in moisture content, whereas the effect of feed was minimal. The cutting efficiency decreased with an increase in the stalk feed rate and moisture content. A moisture content of 30.98% and feed of 3.75 stalks were found optimal, close to the moisture content of 31% and feed of 4 stalks and recommended for the best performance of the machine.